SELF-CONTROL AND LONELINESS WITH NOMOPHOBIA TENDENCIES AMONG TEENAGERS - Zuhriyah, Nikmatuz (jfpublisher, 2024)
The use of smartphones is immense and continues to increase, causing new problems to emerge, especially in health. The increasing intensity of smartphone use also has an impact on daily life. Individuals who are dependent on their cell phones and feel anxious if the cell phone is not nearby are known as Nomophobia or No Mobile Phone Phobia. This research aims to determine the influence between self-control and loneliness with nomophobia tendencies in teenagers. The subjects of this research were early teenagers with a range of ages 12-15 years, totaling 163 subjects. The sampling technique used the g-power application with an effect size of 0.3, power 0.90 and error prob 0.05. Using the SPSS IBM25 Windows application, the data analysis method included multiple regression analysis. The findings of this research suggest that the first hypothesis which claims that there is a tendency between self-control and loneliness and nomophobia in teenagers is accepted. The second hypothesis which states that there is a relationship between self-control and nomophobia in teenagers is acceptable. The third hypothesis which argues that there is a relationship between loneliness and nomophobia in teenagers is accepted.